BRAIN GYM TERHADAP PERKEMBANGAN VERBAL PADA ANAK USIA PRA SEKOLAH DI TK NURUL INSANI MANDURO NGORO MOJOKERTO - Nurun Ayati Khasanah; Ferilia Adiesti; Citra Adityarini Safitri (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
The success of optimal child growth and development determines the nation's future. Speaking or language is a child's ability to be able to understand prohibitions/orders to express wishes, tell stories, ask questions, tell feelings or emotions, various stories to WHO arguments in 2018 Child development in Indonesia is 7,512.6 per 100,000 population or 7.5%, children Delayed development is estimated at approximately 5% to 10% of development. The exact data indicating the delay is not yet known. However, it is estimated that 1 to 3% of children under 5 years of age experience delays. One method of stimulating children is Brain Gym exercise. The study aimed to determine the effect of Brain gym on verbal development in preschool-age children.this type of quantitative research with One Groups Pretest-Posttest Design. The research subjects of group A Nurul Insani Kindergarten children were 23 boys and 17 girls. Children's verbal ability is obtained from observation with KPSP. Held in August – November 2021. analysed by statistical tests using the Wilcoxon test with the results of value (0.01 < 0.05) so that it is concluded that there is an influence of Brain Gym on verbal development in pre-school age children. Brain Gym effectively improves verbal skills in early childhood.further research for more variables about Brain Gym on the development and growth of pre-school age children.